Analysis of Immunization and Immunization Coverage in Children's Outpatient Clinics of Any Type (Public or Private): Cross-Sectional Study - Polina R. Grinchik; Leyla S. Namazova-Baranova; Marina V. Fedoseenko; Elena A. Vishneva; Mariya V. Fominykh; Elena D. Makushina; Nina Y. Plenskovskaya; Tatiana E. Privalova; Alexey Yu. Rtishchev; Dina S. Rusinova ("Paediatrician" Publishers LLC, 2022)
Background. Worldwide private health care system plays significant role in promoting immunization programs for the children population. The role of private medical facilities in Russia in combating children vaccination issues has not been previously studied.Objective. The aim of the study is to study immunization and immunization coverage in children population according to the national immunization schedule (NIS) in outpatient clinics of different forms of property.Methods. The study of medical documentation of children in private (n = 1) and public (n = 2) facilities in Moscow and Moscow region was performed. Immunization (complete vaccination course in those who should be vaccinated by age) and immunization coverage (at least one dose of vaccine by those who have to be vaccinated) were estimated against the NIS schemes according to the data from preventive vaccination cards (form 063/y) and from preventive vaccination lists (form 112/y).Results. The study includes 313 cards of children from private outpatient clinic and 305 - from public outpatient clinic. Immunization and immunization coverage of children against tuberculosis were similar in these facilities: 293 (94%) and 294 (96%) (p = 0.114), respectively, as well as immunization coverage against hepatitis B - in 282 (90%) and 269 (88%) (p = 0.448). Rates of immunization and immunization coverage against the remaining NIS infections were higher in the private clinic. Maximum differences were noted in immunization (178 (57%) in private and 19 (6%) in public facilities; p < 0.001) and immunization coverage (238 (76%) and 52 (17%), respectively; p < 0.001) against pneumococcal disease. Immunization coverage of children for epidemic indications was also higher in private clinic: the largest differences were in immunization against hemophilic and meningococcal infections.Conclusion. Children followed up in private outpatient clinic have higher immunization and immunization coverage rates against most of the NIS infections.